Cost‐Effective Identification of Hepatocellular Carcinoma from Cirrhosis or Chronic Hepatitis Virus Infection Using Eight Methylated Plasma DNA Markers - Tian Yang; Mingda Wang; Nanya Wang; Mingxin Pan; Yu Xu; Qiancheng You; Lanqing Yao; Jiahao Xu; Lihui Gu; Xiaodong Sun; Lei Zhang; Jiayue Xu; et al. (Advanced Science)
Abstract Early detection of hepatocellular carcinoma (HCC) in patients with liver cirrhosis (LC) and/or hepatitis virus B/C infection (HVI) improves survival, highlighting the need for accurate, affordable diagnostic tools. Here, 11 methylated DNA markers (MDMs) are identified during marker discovery. In phase I, each selected MDM is validated in 175 plasma samples (HCC, n = 85; LC/HVI, n = 72) by the CO‐methylation aMplification rEal‐Time PCR (COMET) assay. Of these, 8 MDMs are qualified for phase II study, where a logistic regression model (COMET‐LR) is trained and validated with 336 plasma samples (HCC, n = 211; LC/HVI, n = 113; training vs validation, 2:1). In the validation, the COMET‐LR achieved 90.0% sensitivity at 97.4% specificity. Notably, sensitivity in patients with TNM stage I, diameter<3 cm, AFP‐negative (<20 ng mL−1), PIVKA‐II‐negative (<40 mAU mL−1) is 82.4%, 77.8%, 88.6%, and 85.7%, respectively. The COMET‐LR outperformed multiple protein markers (AFP, AFP‐L3, and PIVKA‐II) and published scores for HCC screening (GALAD, Doylestown, and ASAP), in terms of both sensitivity and specificity. The assay represents a significant advancement in addressing the unmet need for accurate, non‐invasive, accessible, and cost‐effective early detection tools for LC/HVI individuals. Further validation in a prospective cohort is warranted.